Social Media in Southeast Turkey - Costa, Elisabetta (Why We Post, 2016)
This book presents an ethnographic study of social media in Mardin, a medium-sized town located in the Kurdish region of Turkey. The town is inhabited mainly by Sunni Muslim Arabs and Kurds, and has been transformed in recent years by urbanisation, neoliberalism and political events. Elisabetta Costa uses her 15 months of ethnographic research to explain why public-facing social media is more conservative than offline life. Yet, at the same time, social media has opened up unprecedented possibilities for private communications between genders and in relationships among young people - Costa reveals new worlds of intimacy, love and romance. She also discovers that, when viewed from the perspective of people's everyday lives, political participation on social media looks very different to how it is portrayed in studies of political postings separated from their original complex, and highly socialised, context.